Friar Francisco de Osuna's "Norte de los estados" in modernized Spanish : a practical guide to conjugal life in sixteenth-century Europe /: a practical guide to conjugal life in sixteenth-century Europe. (2019) - Osuna, Francisco de, approximately 1540
No abstract available